English as a Lingua Franca and Its Impact on Social Integration in Conditions of Global Migration - Altaany, Haitham M; T Abadel, Raba’a; Youssof Al Saati , Maan; Khalaf Sakr, Ahmed Mohi; Abdelbary, Osama (Forum for Linguistic Studies, 2025)
Multicultural and migrant-receiving societies rely on the English language to integrate their populations. As the world’s dominant language, English is essential for gaining access to employment, public services, and supporting community life—all crucial for successful integration. This review analyzed 32 published studies and policy reports from 2003 to 2025 to assess how English proficiency affects social inclusion for immigrants, refugees, and minority groups. Using systematic literature review methods, the authors employed thematic content analysis to identify recurring themes in employment, education, peer involvement, and identity development. The findings indicate that strong English skills help individuals engage more actively in their communities, improve employment prospects, participate in politics, and foster social cohesion. However, numerous challenges hinder language acquisition, including the high cost of schooling, cultural and mindset barriers, and social hostility. The study emphasizes the importance of a whole-school approach to language learning, incorporating culturally sensitive teaching, diverse learning experiences, and necessary policy reforms. Ultimately, the authors provide recommendations for educators, policymakers, and community organizations to enhance the role of English in promoting equal and inclusive societies. Despite widespread recognition of English’s global role, its urgent relevance lies in the increasing migration flows and the need for effective integration strategies. The novelty of this study is its focus on the social impact of English proficiency for migrants, particularly in terms of inclusion and empowerment. The core problem addressed is the lack of equitable access to language education and its consequences for immigrant, refugee, and minority populations.